Seasonal variations of glacier seismicity at the tongue of Rhonegletscher (Switzerland) with a focus on basal icequakes - Dalban Canassy, Pierre; Röösli, Claudia; Walter, Fabian (International Glaciological Society, 2016)
Fractured systems developing at the base of temperate glaciers play a significant role in the transport of subglacial water. Their influence on dynamics and hydraulics of glaciers and the seasonal alterations they experience during the hydrological year, remain however, poorly understood, as they lay beyond the reach of most conventional glaciological techniques. In this work, we investigate the seasonal evolution of glacier seismicity in the ablation zone of Rhonegletscher (Switzerland) and focus on basal fracture processes. To do this, we use seismic measurements performed between June 2012 and July 2013 and complementary measurements of surface motion and changes in melt water input inferred from degree day modeling. Results of a spectrogram analysis highlight predominant seismic emissions until end of October 2012 and from mid April 2013 in line with measured surface velocities, and indicate a rapid adaptation of the basal drainage system at initiation and end of the winter period. The analysis of icequakes emitted from two active regions shows that the basal events, due to opening and closing of cracks within fracture networks, persist after winter initiation, and points out the year-long preservation of the associated sources. In this regard, we deduce that basal crack networks aseismically evolve during the winter period. ISSN:0022-1430 ISSN:1727-5652